Wage Flexibility in Turbulent Times : A Practitioner's Guide, with an Application to Poland. (IMF Working Papers; Working Paper ;, 2005)
This paper reviews several methods to measure wage flexibility, and their suitability for evaluating the extent of such flexibility during times of structural change, when wage distributions and wage curves can be particularly volatile. The paper uses nonparametric estimation to capture possible nonlinearities in the wage curve and relaxes the assumption of a stable wage distribution over time by linking the shape of the wage change distribution to macroeconomic variables. The proposed methodology is applied to Polish micro data. The estimates confirm that wages are less elastic in a high-unemployment/low-wage environment. Based on a comparison of actual and counterfactual wage distributions, the effects of nominal wage rigidities on real wages, and thus, on the labor market and the real economy, were limited until 1998, but have been quite significant thereafter.